2009
DOI: 10.1002/ajh.21491
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thrombi are not detected by 3D magnetic resonance angiography in adults with sickle cell anemia and an elevated triscuspid regurgitant jet velocity

Abstract: An elevated tricuspid regurgitant jet (TRJ) velocity is present in more than 30% of adults with sickle cell anemia (SCA) and is associated with a risk of death [1][2][3][4]. The contribution of pulmonary thrombi to an elevated TRJ velocity is not well defined. To evaluate the relationship between an elevated TRJ velocity and pulmonary thrombi, we performed 3D, contrast-enhanced magnetic resonance angiography (3D MRA) in nine adults with SCA. Of the six participants with an elevated TRJ velocity, 5 (83%) did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…15, 37, 38 Prior studies have concluded that chronic thromboembolic disease as defined by V/Q scan 39 or magnetic resonance angiography 40 is not common in sickle cell disease patients with tricuspid regurgitant jet velocity ≥ 2.5 m/s. However, studies in sickle cell disease patients with catheterization-confirmed pulmonary hypertension will be needed to definitively determine the contribution of chronic thromboemboli to pulmonary hypertension and to evaluate the relationship between venous thromboembolism and high pulmonary pressures.…”
Section: Discussionmentioning
confidence: 99%
“…15, 37, 38 Prior studies have concluded that chronic thromboembolic disease as defined by V/Q scan 39 or magnetic resonance angiography 40 is not common in sickle cell disease patients with tricuspid regurgitant jet velocity ≥ 2.5 m/s. However, studies in sickle cell disease patients with catheterization-confirmed pulmonary hypertension will be needed to definitively determine the contribution of chronic thromboemboli to pulmonary hypertension and to evaluate the relationship between venous thromboembolism and high pulmonary pressures.…”
Section: Discussionmentioning
confidence: 99%